1999
DOI: 10.1115/1.483187
|View full text |Cite
|
Sign up to set email alerts
|

Internal Reforming Solid Oxide Fuel Cell-Gas Turbine Combined Cycles (IRSOFC-GT): Part A—Cell Model and Cycle Thermodynamic Analysis

Abstract: The aim of this work is to investigate the performance of internal reforming solid oxide fuel cell (IRSOFC) and gas turbine (GT) combined cycles. To study complex systems involving IRSOFC a mathematical model has been developed that simulates the fuel cell steady-state operation. The model, tested with data available in literature, has been used for a complete IRSOFC parametric analysis taking into account the influence of cell operative pressure, cell and stream temperatures, fuel-oxidant flow rates and compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(58 citation statements)
references
References 13 publications
0
58
0
Order By: Relevance
“…The capability of SOFC to internally reform hydrocarbon fuels (mostly CH 4 ) provides SOFC-based systems more flexibility in fuel input [5][6][7][8]. Thus, recently much research and development attention has been paid to SOFC-based IGFC systems.…”
Section: Igfc Development: a Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The capability of SOFC to internally reform hydrocarbon fuels (mostly CH 4 ) provides SOFC-based systems more flexibility in fuel input [5][6][7][8]. Thus, recently much research and development attention has been paid to SOFC-based IGFC systems.…”
Section: Igfc Development: a Literature Reviewmentioning
confidence: 99%
“…This efficiency goal as set by the DOE is to account for any penalty associated with CO 2 separation but not that due to its compression to the sequestration pressure. Previous conceptual analyses of such IGFC plants have clearly shown the potential for improved efficiency and emissions relative to other system approaches [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], yet none of the research work published to date have demonstrated this performance goal, mostly due to the fact that even with highly efficient SOFC as the power block, CO 2 separation and the gasification process posed significant efficiency penalties on the system. Besides, integration of an SOFC power block with a gasification system is very different from the integration of gas turbine and steam turbine power blocks that are typical of an integrated gasification combined cycle (IGCC) plant due to the unique operating and control features of SOFC stacks.…”
Section: Introductionmentioning
confidence: 99%
“…Two different possibilities are available to connect SOFCs and gas turbine technologies [3,4]: atmospheric ( Figure 1) or pressurised ( Figure 2). In the first case the operative pressure of the stack is atmospheric, while in the second case the stack operates at the same pressure as the gas turbine cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In the SOFC/GT hybrid system, the fuel cell high temperature SOFC exhaust drives a gas turbine, providing air flow and pressurizing the SOFC while driving an electric generator that produces additional electrical power. As a result, SOFC/GT hybrid systems have demonstrated efficiencies above 50% [5,18] and studies have shown the possibility for electrical conversion above 70% [4,19] when operating on natural gas and above 60% in an integrated coal gasification plant [6,19]. Higher efficiency reduces CO 2 emissions while separated fuel and air flows in the SOFC allow system designs for CO 2 sequestration with minimal performance cost [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…These societal issues, coupled with the ever growing demands of an energy intensive lifestyle, highlight the insufficiencies of current power generation technologies. Hybrid solid oxide fuel cell/gas turbine (SOFC/GT) technology is a continuous generation technology that offers the possibility of higher efficiency combined with lower emissions [1][2][3][4]. Commercialization of advanced hybrid SOFC/GT technology requires considerable improvement of core component (e.g., pressurized SOFC) performance, system integration, and dynamical control [5][6][7].…”
Section: Introductionmentioning
confidence: 99%